2013
DOI: 10.1158/1078-0432.ccr-13-1106
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody against Cell Surface GRP78 as a Novel Agent in Suppressing PI3K/AKT Signaling, Tumor Growth, and Metastasis

Abstract: Purpose The ER chaperone GRP78 translocates to the surface of tumor cells and promotes survival, metastasis, and resistance to therapy. An oncogenic function of cell surface GRP78 has been attributed to the activation of phosphoinositide 3-kinase (PI3K) pathway. We intend to use a novel anti-GRP78monoclonal antibody (MAb159) to attenuate PI3K signaling and inhibit tumor growth and metastasis. Experimental Design MAb159 was characterized biochemically. Anti-tumor activity was tested in cancer cell culture, tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
143
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(153 citation statements)
references
References 33 publications
(52 reference statements)
8
143
0
2
Order By: Relevance
“…Subsequently, it was demonstrated that the cell-surface form of GRP78 (scGRP78) complexes with PI3K to promote phosphatidylinositol (3-5)-trisphosphate formation (18). Targeting csGRP78 with a monoclonal antibody led to suppression of AKT signaling and tumor growth (45,46). CsGRP78 is also an obligatory binding partner for Cripto, a GPI-anchored cell-surface protein and an upstream regulator of the TGFβ pathway and of AKT (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was demonstrated that the cell-surface form of GRP78 (scGRP78) complexes with PI3K to promote phosphatidylinositol (3-5)-trisphosphate formation (18). Targeting csGRP78 with a monoclonal antibody led to suppression of AKT signaling and tumor growth (45,46). CsGRP78 is also an obligatory binding partner for Cripto, a GPI-anchored cell-surface protein and an upstream regulator of the TGFβ pathway and of AKT (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Blockade of cell surface GRP78 inhibited the proliferation and induced apoptosis in melanoma and prostate cancer. 26,27 Inhibition of cell surface GRP78 inhibited the tumor invasion and metastasis in hepatocellular carcinoma and colorectal cancer cell. [28][29][30] Nowadays, cell surface GRP78 is regarded as a potential target for the targeted therapy of many human cancers.…”
mentioning
confidence: 99%
“…However, the natural GRP78 IgM has a low binding affinity and a restricted binding repertoire. To resolve this problem, a monoclonal anti-GRP78 antibody, mAb159, has been developed, and it can inhibit tumor growth and metastasis by modulating the PI3K pathway (56).…”
Section: Discussionmentioning
confidence: 99%
“…Passive transfer of antitumor antibodies offers a more efficient therapeutic modality. For example, a humanized monoclonal anti-GPR78 antibody (mAb159) that has shown inhibitory activity for CRC (56) has been developed. Patients with normal immunity who have cancer may negatively select out B cells with high activities against autoantigens, resulting in lowactivity EAAs.…”
Section: Discussionmentioning
confidence: 99%